2016
DOI: 10.1002/cplu.201600088
|View full text |Cite
|
Sign up to set email alerts
|

A Threefold Interpenetrated Pillared‐Layer Metal–Organic Framework for Selective Separation of C2H2/CH4 and CO2/CH4

Abstract: A new threefold interpenetrated pillared‐layer microporous metal–organic framework, [Zn2(cca)2(4‐bpdb)]n⋅(DMF)2n (UTSA‐85) (H2cca=4‐carboxycinnamic acid, 4‐bpdb=1,4‐bis(4‐pyridyl)‐2,3‐diaza‐1,3‐butadiene, and DMF=N,N‐dimethylformamide), has been designed and generated by the solvothermal reaction of mixed ligands (H2cca and 4‐bpdb) and Zn(NO3)2⋅6 H2O. Single‐crystal XRD analysis disclosed that discrete paddle‐wheel Zn2(COO)4 clusters as secondary building units linked the cca ligands to give two‐dimensional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The CO 2 /N 2 and CO 2 /CH 4 selectivities increased with temperature and the exact reason is still unclear . The functional azine sites might play some roles through different interactions with those gas molecules . Both the CO 2 /N 2 and CO 2 /CH 4 selectivity values are higher than those of previously reported MOFs: PCN‐88 (CO 2 /N 2 : 18/296 K, CO 2 /CH 4 : 5/296 K), PCN‐61 (CO 2 /N 2 : 15/298 K), Cu 24 (TPBTM) 8 (CO 2 /N 2 : 22/298 K), ZJNU‐44a (CO 2 /N 2 : 15/296 K, CO 2 /CH 4 : 5.5/296 K), SIFSIX‐2‐Cu (CO 2 /N 2 : 13.7/298 K, CO 2 /CH 4 : 5.3/298 K), HKUST‐1 (CO 2 /N 2 : 101/293 K), PMOF‐3a (CO 2 /N 2 : 29.2/273 K and 23.4/296 K, CO 2 /CH 4 : 8/273 K and 5.1/296 K), JUC‐141 (CO 2 /N 2 : 21.6/273 K and 27.6/298 K, CO 2 /CH 4 : 4.2/273 K and 8.7/298 K), Cu‐BTTri (CO 2 /N 2 : 21/298 K), en‐Cu‐BTTri (CO 2 /N 2 : 25/298 K), NOTT‐202a (CO 2 /N 2 : 26.7/273 K and 4.3/293 K, CO 2 /CH 4 : 2.9/273 K and 1.4/293 K), MOF‐177 (CO 2 /N 2 : 3.6/296 K), Bio‐MOF‐11 (CO 2 /N 2 : 79.5/296 K), Zn‐MOF‐74 (CO 2 /N 2 : 87.7/296 K, CO 2 /CH 4 : 5/296 K), In 2 X (CO 2 /CH 4 : 6.4/273 K and 5.6/298 K), Tb(BCB), (CO 2 /CH 4 : 4.1/273 K and 2.3/296 K), InOF‐14 (CO 2 /CH 4 : 3.1/273 K and 2.4/295 K), many ZIF materials (ZIF‐68, CO 2 /N 2 : 18.7/298 K, CO 2 /CH 4 : 5/298 K; ZIF‐69, CO 2 /N 2 : 19.9/298 K, CO 2 /CH 4 : 5.1/298 K) and benchmark zeolite Cu‐SSZ13 (CO 2 /N 2 : 67.4/296 K), zeolite MFI (CO 2 /N 2 : 11.2/296 K) under the similar conditions (Table S4, Supporting Information) ,.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The CO 2 /N 2 and CO 2 /CH 4 selectivities increased with temperature and the exact reason is still unclear . The functional azine sites might play some roles through different interactions with those gas molecules . Both the CO 2 /N 2 and CO 2 /CH 4 selectivity values are higher than those of previously reported MOFs: PCN‐88 (CO 2 /N 2 : 18/296 K, CO 2 /CH 4 : 5/296 K), PCN‐61 (CO 2 /N 2 : 15/298 K), Cu 24 (TPBTM) 8 (CO 2 /N 2 : 22/298 K), ZJNU‐44a (CO 2 /N 2 : 15/296 K, CO 2 /CH 4 : 5.5/296 K), SIFSIX‐2‐Cu (CO 2 /N 2 : 13.7/298 K, CO 2 /CH 4 : 5.3/298 K), HKUST‐1 (CO 2 /N 2 : 101/293 K), PMOF‐3a (CO 2 /N 2 : 29.2/273 K and 23.4/296 K, CO 2 /CH 4 : 8/273 K and 5.1/296 K), JUC‐141 (CO 2 /N 2 : 21.6/273 K and 27.6/298 K, CO 2 /CH 4 : 4.2/273 K and 8.7/298 K), Cu‐BTTri (CO 2 /N 2 : 21/298 K), en‐Cu‐BTTri (CO 2 /N 2 : 25/298 K), NOTT‐202a (CO 2 /N 2 : 26.7/273 K and 4.3/293 K, CO 2 /CH 4 : 2.9/273 K and 1.4/293 K), MOF‐177 (CO 2 /N 2 : 3.6/296 K), Bio‐MOF‐11 (CO 2 /N 2 : 79.5/296 K), Zn‐MOF‐74 (CO 2 /N 2 : 87.7/296 K, CO 2 /CH 4 : 5/296 K), In 2 X (CO 2 /CH 4 : 6.4/273 K and 5.6/298 K), Tb(BCB), (CO 2 /CH 4 : 4.1/273 K and 2.3/296 K), InOF‐14 (CO 2 /CH 4 : 3.1/273 K and 2.4/295 K), many ZIF materials (ZIF‐68, CO 2 /N 2 : 18.7/298 K, CO 2 /CH 4 : 5/298 K; ZIF‐69, CO 2 /N 2 : 19.9/298 K, CO 2 /CH 4 : 5.1/298 K) and benchmark zeolite Cu‐SSZ13 (CO 2 /N 2 : 67.4/296 K), zeolite MFI (CO 2 /N 2 : 11.2/296 K) under the similar conditions (Table S4, Supporting Information) ,.…”
Section: Resultsmentioning
confidence: 83%
“…The results of IAST calculations have shown that under 1 bar, the selectivity for CO 2 /N 2 mixture is 57 at 273 K and 121.4 at 295 K; the selectivity for CO 2 /CH 4 mixture is 8.4 at 273 K and 8.8 at 295 K (Figure (c) and 3(f)). The CO 2 /N 2 and CO 2 /CH 4 selectivities increased with temperature and the exact reason is still unclear . The functional azine sites might play some roles through different interactions with those gas molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Both CO 2 /N 2 and CO 2 /CH 4 selectivity at different temperatures and desired pressures with methods of selectivity calculations (IAST, isotherm slopes, Henry Law) based on through literature survey is presented in Table S4, Supporting Information. The selectivities increased with pressure and the exact reason is still unclear,,,,,, however, this might be attributed to different adsorption sites in the framework that are successively occupied with increasing pressure. It is worth mentioning that IITKGP‐8 a has the modest CO 2 uptake capacity but displays a higher CO 2 /N 2 selectivity and moderate CO 2 /CH 4 selectivity, underlying the uniqueness of this new MOF for potential application in carbon capture and separation from landfill gas and flue gas as well.…”
Section: Resultsmentioning
confidence: 98%
“…For example, Zn MOFs [Zn 2 (1,4-bdc) 2 (dabco)] and [Zn 2 (1,4-bdc) 2 (bpy)], where 1,4-H 2 bdc = benzene-1,4-dicarboxylic acid, dabco = diazabicyclo[2.2.2]octane, and bpy = 4,4′-bipyridine, both show pcu and kag net topologies [22]; such results are tentatively attributed to the degree of deviation of the conformations of the paddlewheel SBUs. Of note, this also suggests that judicially designed and modified MOFs may be promising porous materials for applications in gas adsorption such as carbon dioxide (CO 2 ) capture [2,3,4,5,23,24,25,26,27,28,29,30]. For example, Zn MOF [Zn 2 (cca)(4-bpdb) 2 ] (H 2 cca = 4-carboxycinnamaic acid, 4-bpdb = 1,4-bis(4-pyridyl)-2,3-diaza-1,3-butadiene) has shown noticeable CO 2 uptakes of 54.2 cm 3 /g at 273 K and 38.9 cm 3 /g at 298 K [30].…”
Section: Introductionmentioning
confidence: 99%